2022
DOI: 10.1021/acs.chemrestox.2c00110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Common e-Liquid Flavorants and Added Nicotine on Toxicant Formation during Vaping Analyzed by 1H NMR Spectroscopy

Abstract: A broad variety of e-liquids are used by e-cigarette consumers. Additives to the e-liquid carrier solvents, propylene glycol and glycerol, often include flavorants and nicotine at various concentrations. Flavorants in general have been reported to increase toxicant formation in e-cigarette aerosols, yet there is still much that remains unknown about the effects of flavorants, nicotine, and flavorants + nicotine on harmful and potentially harmful constituents (HPHCs) when aerosolizing e-liquids. Common flavoran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The data on carbonyl and phenol emissions showed mixed observations with increase in some emissions and decrease in others for the same e-liquid condition. This could be attributed to the different mechanisms of formation during e-cigarette operation,26 27 or to coil variability in triplicate measurements that can mask the impact of liquid ingredients on emissions 28. Also, focusing on toxicants that are mainly formed from PG/G degradation23 24 29 may lead to overlooking other degradation pathways, as in the case of sucralose leading to chloropropanols 28 30.…”
Section: Discussionmentioning
confidence: 99%
“…The data on carbonyl and phenol emissions showed mixed observations with increase in some emissions and decrease in others for the same e-liquid condition. This could be attributed to the different mechanisms of formation during e-cigarette operation,26 27 or to coil variability in triplicate measurements that can mask the impact of liquid ingredients on emissions 28. Also, focusing on toxicants that are mainly formed from PG/G degradation23 24 29 may lead to overlooking other degradation pathways, as in the case of sucralose leading to chloropropanols 28 30.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of e‐liquids has been analysed previously by high‐performance liquid chromatography (HPLC), for example, to identify carbonyls in toxic chemicals like formaldehyde 20 . Peyton et al used 1 H NMR spectroscopy to investigate the effect of both nicotine and flavourings on toxicant formation during vaping and found that the presence of such compounds could enhance PG and VG degradation 21 . GC‐MS allows the direct analysis of volatiles and has been widely demonstrated to be a viable method for e‐liquids 12,22–26 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Peyton et al used 1 H NMR spectroscopy to investigate the effect of both nicotine and flavourings on toxicant formation during vaping and found that the presence of such compounds could enhance PG and VG degradation. 21 GC-MS allows the direct analysis of volatiles and has been widely demonstrated to be a viable method for e-liquids. 12,[22][23][24][25][26] This technique offers the separation capability of chromatography, required as liquids increasingly contain more complex flavouring components, and the identification abilities of MS. Coupling of GC-MS with a headspace (HS) analyser has the additional benefit of direct sample introduction of the vapour, formed above the e-liquid on heating.…”
mentioning
confidence: 99%
“…The most common determination methods are based on gas chromatography in combination with different detectors, either flame ionization [18][19][20] or mass spectrometry [21,22]. Some of the techniques for the determination of glycerol, propylene glycol, and nicotine are based on proton nuclear magnetic resonance ( 1 HNMR) [23][24][25]. Despite these efforts, to the best of the author's knowledge, there is no method that uses liquid chromatography coupled with mass spectrometry (LC-MS) or tandem mass spectrometry (LC-MS/MS) in determination of nicotine, propylene glycol, and glycerol.…”
Section: Introductionmentioning
confidence: 99%